Measurements of δ13C in CH4 and using particle dispersion modeling to characterize sources of Arctic methane within an air mass. Issue 23 (13th December 2016) - France, J. L.; Cain, M.; Fisher, R. E.; Lowry, D.; Allen, G.; O'Shea, S. J.; Illingworth, S.; Pyle, J.; Warwick, N.; Jones, B. T.; Gallagher, M. W.; Bower, K.; et al.
Abstract: A stratified air mass enriched in methane (CH4 ) was sampled at 600 m to 2000 m altitude, between the north coast of Norway and Svalbard as part of the Methane in the Arctic: Measurements and Modelling campaign on board the UK's BAe‐146‐301 Atmospheric Research Aircraft. The approach used here, which combines interpretation of multiple tracers with transport modeling, enables better understanding of the emission sources that contribute to the background mixing ratios of CH4 in the Arctic. Importantly, it allows constraints to be placed on the location and isotopic bulk signature of the emission source(s). Measurements of δ 13 C in CH4 in whole air samples taken while traversing the air mass identified that the source(s) had a strongly depleted bulk δ 13 C CH4 isotopic signature of −70 (±2.1)‰. Combined Numerical Atmospheric‐dispersion Modeling Environment and inventory analysis indicates that the air mass was recently in the planetary boundary layer over northwest Russia and the Barents Sea, with the likely dominant source of methane being from wetlands in that region. Key Points: Northern Russian wetlands can contribute notably to methane in the remote Arctic Isotopic bulk signature of 13 CH4 determined in air mass with enhanced methane observed in the Arctic Isotopic source signature for δ 13 C for CH4 bulk input from northern Russian wetlands and potential shallow shelf region offshore is <−70‰